2006
DOI: 10.1097/01.aud.0000194515.28023.4b
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Cochlear Implants in Children: Localization Acuity Measured with Minimum Audible Angle

Abstract: Children with sequential BI cochlear implants represent a unique population of individuals who have undergone variable amounts of auditory deprivation in each ear. Our findings suggest that many but not all of these children perform better on measures of localization acuity with two cochlear implants compared with one and are better at the task than children using the cochlear implant + hearing aid. These results must be interpreted with caution, because benefits on other tasks as well as the long-term benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
179
6
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(196 citation statements)
references
References 46 publications
8
179
6
3
Order By: Relevance
“…None of the 8 participants who used only one cochlear implant could correctly localize sound sources even at the maximum angle tested (70º). Litovsky (2006a) similarly showed that 9 out of 13 pediatric bilateral implant users had minimum audible angles less than 40º and of these, 8 could distinguish angles smaller than 20º. Two of six children using one implant and one hearing aid had MAAs similar to the bilateral implant users, but the remaining children in this group performed much worse than the average child with bilateral implants.…”
Section: Usersmentioning
confidence: 85%
See 3 more Smart Citations
“…None of the 8 participants who used only one cochlear implant could correctly localize sound sources even at the maximum angle tested (70º). Litovsky (2006a) similarly showed that 9 out of 13 pediatric bilateral implant users had minimum audible angles less than 40º and of these, 8 could distinguish angles smaller than 20º. Two of six children using one implant and one hearing aid had MAAs similar to the bilateral implant users, but the remaining children in this group performed much worse than the average child with bilateral implants.…”
Section: Usersmentioning
confidence: 85%
“…Further, Galvin and colleagues (Galvin et al 2007) reported that children who received their second CI after 4 years of age did not show any improvement using both implants over unilateral conditions on tests of sound localization after 6-13 months of bilateral experience. Litovsky (Litovsky et al 2006a;Litovsky et al 2006b;Litovsky et al 2004) also report high degrees of variability within groups of implanted children, which could not always be attributed to duration of deafness or length of bilateral implant use. In order to better predict and promote improved outcomes with bilateral cochlear implants, further research is needed to gain understanding into what factors determine localization abilities in these children.…”
Section: Usersmentioning
confidence: 99%
See 2 more Smart Citations
“…Other novel applications of cochlear implants currently being studied include the use of bilateral implants or bimodal stimulation to improve localization ability (van Hoesel and Tyler, 2003;Seeber et al, 2004;Verschuur et al, 2005;Litovsky et al, 2006), speech perception in the presence of noise (Au et al, 2003;van Hoesel and Tyler, 2003;Vermeir et al, 2003;Ching et al, 2004;Ramsden et al, 2005) and the creation of "virtual channels" by proportionally dividing stimulus current between two or more electrode sites to generate a potentially large number of perceptually distinct pitches using a minimum number of electrode sites (McDermott and McKay, 1994;Donaldson et al, 2005;Kwon and van den Honert, 2006). In each of these areas animal experiments could play an important role in understanding the complex interactions between multiple inputs and how specific electrode design features might be optimized for each purpose.…”
Section: Future Directionsmentioning
confidence: 99%